NiNC Catalysts in CO2-to-CO Electrolysis - Zhang, Hao; Qi, Menghui; Wang, Yong (Nano-Micro Letters, 2024)
CO2-to-CO electrolyzer technology converts carbon dioxide into carbon monoxide using electrochemical methods, offering significant environmental and energy benefits by aiding in greenhouse gas mitigation and promoting a carbon circular economy. Recent study by Strasser et al. in Nature Chemical Engineering presents a high-performance CO2-to-CO electrolyzer utilizing a NiNC catalyst with nearly 100% faradaic efficiency, employing innovative diagnostic tools like the carbon crossover coefficient (CCC) to address transport-related failures and optimize overall efficiency. Strasser’s research demonstrates the potential of NiNC catalysts, particularly NiNC-IMI, for efficient CO production in CO2-to-CO electrolyzers, highlighting their high selectivity and performance. However, challenges such as localized CO2 depletion and mass transport limitations underscore the need for further optimization and development of diagnostic tools like CCC. Strategies for optimizing catalyst structure and operational parameters offer avenues for enhancing the performance and reliability of electrochemical CO2 reduction catalysts. Highlights: 1 NiNC catalysts achieve nearly 100% faradaic efficiency in CO2-to-CO conversion. 2 The carbon crossover coefficient is introduced as a diagnostic tool for performance optimization. 3 Tandem electrolyzer design and mesoporous structures enhance product yields and efficiency.